A prophet like Moses: prophecy, law, and Israelite religion - Stackert, Jeffrey (Oxford University Press, 2014)
'A Prophet Like Moses' addresses two of the oldest and most persistent problems in biblical studies: the relationship between prophecy and law in the Hebrew Bible and the utility of the Documentary Hypothesis for understanding Israelite religion. These topics have in many ways dominated pentateuchal studies and the investigation of Israelite religion since the 19th century, culminating in Julius Wellhausen's influential 'Prolegomena to the History of Ancient Israel'. Setting its inquiry against this backdrop while drawing on and extending recent developments in pentateuchal theory, this study tackles its subject through an investigation of the different presentations of Mosaic prophecy in the four Torah sources.